2021
DOI: 10.3390/ijerph18168385
|View full text |Cite
|
Sign up to set email alerts
|

Is Experience the Best Teacher? Knowledge, Perceptions, and Awareness of Wildfire Risk

Abstract: Wildfires represent a natural phenomenon with detrimental effects on natural resources and human health. A better knowledge, perception, and awareness of wildfire risk may help communities at risk of exposure to prevent future events and safeguard their own lives. The aim of this study is to explore differences between individuals with and without previous wildfire experience, in terms of (1) subjective and advanced wildfire knowledge, (2) self-reported perceptions, (3) level of information, (4) self-protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…This may be for the obvious reason that experience is the best teacher and as such respondents with relatively long experience in the CE space would know more about the inner workings of CE than those who are relatively new to the CE space. This result is partially supported by findings by Spano et al (2021) in which they revealed that individuals with significant prior experience had a higher level of subject knowledge on wildfires which was the subject of discussion. Spano et al (2021), however, noted that the extent of knowledge depended on the depth of discussion in that there was no significant difference in knowledge level when more advanced aspects were asked.…”
Section: Stakeholder Roles In the Ce Transitionsupporting
confidence: 63%
See 1 more Smart Citation
“…This may be for the obvious reason that experience is the best teacher and as such respondents with relatively long experience in the CE space would know more about the inner workings of CE than those who are relatively new to the CE space. This result is partially supported by findings by Spano et al (2021) in which they revealed that individuals with significant prior experience had a higher level of subject knowledge on wildfires which was the subject of discussion. Spano et al (2021), however, noted that the extent of knowledge depended on the depth of discussion in that there was no significant difference in knowledge level when more advanced aspects were asked.…”
Section: Stakeholder Roles In the Ce Transitionsupporting
confidence: 63%
“…This result is partially supported by findings by Spano et al (2021) in which they revealed that individuals with significant prior experience had a higher level of subject knowledge on wildfires which was the subject of discussion. Spano et al (2021), however, noted that the extent of knowledge depended on the depth of discussion in that there was no significant difference in knowledge level when more advanced aspects were asked. The study also revealed that respondents in higher positions within their organizations as well as those involved in decision-making had more CE knowledge.…”
Section: Stakeholder Roles In the Ce Transitionsupporting
confidence: 63%
“…Knowledge, Perceptions, and Awareness of Wildfire Risk. 2021 [ 53 ]. Examine the impact of direct experience with wildfires on preparedness on the topic of wildfires among individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge, Perceptions, and Awareness of Wildfire Risk. 2021 [ 53 ]. Italy N = 775 participants; n = 260 with direct wildfire experience, and n = 515 without direct wildfire experience Quantitative study.…”
Section: Methodsmentioning
confidence: 99%
“…Only providing information related to the risk of forest fire to the public might not help increase awareness or undertake actions (Kumagai et al, 2004;Slovic, 1999). A recent study stated that both experience and perception of the effective mitigation measures can determine the risk perception and their intention while implementing the measures (Spano et al, 2021). Documenting the perceptions of community forest managers will provide essential insights into the state of knowledge and practice on the adoption of different plans and strategies related to forest fire management (Williamson et al, 2005).…”
Section: Parajuli Et Almentioning
confidence: 99%